Can birth weight predict later body composition in anorexia nervosa? - Mattar, L. (2012)
BACKGROUND/OBJECTIVES: The relationship between birth weight and body composition at later stages in life was not studied previously in anorexia nervosa (AN). The aim of the following brief report is to present results concerning the relationship between birth weight and later body composition specifically in AN, and to check if the programming of body composition from birth weight is still detected in severely emaciated AN patients. SUBJECTS/METHODS: One hundred and fifty-one female AN patients aged between 13 and 44 were recruited from 11 inpatient treatment facilities in France. Birth weight, body weight and height were obtained. Body composition was measured using bioelectrical impedance. Birth weight was significantly correlated to lifetime maximum body mass index (BMI; r ¼ 0.211, P ¼ 0.009) and significantly correlated to fat-free mass index (r ¼ 0.190, P ¼ 0.027) but not to fat mass index (FMI). RESULTS: This report confirms that even in AN when patients are severely emaciated and where fat-free mass (FFM) and fat mass (FM) are low, a link between birth weight and FFM and BMI can still be identified, independently from age. CONCLUSION: Further studies are needed on larger samples exploring other factors, such as gender, puberty and ethnicity.